Rapid Eye Movement Sleep Behavior Disorder Screening Questionnaire in Persian: A Report on the Translation Process - Mehrdad Sadri; Alia Shakiba; Hamed Amiri Fard; Reza Bidaki; Vajiheh Aghamollaii (Journal of Social Behavior and Community Health)
Background: Rapid eye movement sleep behavior disorder (RBD) is a condition where there are changes in muscle tone during REM sleep, leading to abnormal movements. This disorder is typically diagnosed using video polysomnography (VPSG), which is considered the gold standard test. However, a screening questionnaire for RBD (RBDSQ) has been developed, translated, and validated in various languages, and could be used as a low-cost alternative to VPSG. In this study, we followed a standard multi-step process to translate the RBDSQ into Persian. Methods: As per the guidelines suggested by Mapi Research Trust, we followed a four-step process for translation. The process included forward translation, backward translation, cognitive interviews with fifteen patients, and proofreading. We collaborated with Mapi Research Trust in each step of the process. Also, we conducted discussion and revision sessions for each step to ensure that the final translation was accurate. Results: After reviewing the forward and backward translations, some of the items were rephrased. Patients who participated in cognitive interviews found the translation to be generally clear, but some improvements were necessary to make it more expressive. The final proofreading process involved correcting some typing and spelling errors. Conclusions: The Persian translation of RBDSQ was approved by Mapi Research Trust through a standard translation process. This translation is now compatible with the original English version and is available for a future clinical validation study.